Action observation training promotes motor improvement and modulates functional network dynamic connectivity in multiple sclerosis. (January 2021) - Cordani, Claudio; Valsasina, Paola; Preziosa, Paolo; Meani, Alessandro; Filippi, Massimo; Rocca, Maria A
We investigated modifications of resting state dynamic functional network connectivity (dFNC) following a 2-week action observation training (AOT) in 46 right-handed healthy controls (HC) and 41 patients with multiple sclerosis (pwMS) and dominant-hand motor impairment, who were randomized to AOT or control (C) training. PwMS had decreased baseline dFNC versus HC. After training, MS groups improved in right upper limb functions, mainly in AOT, and showed dFNC increase (larger in MS-AOT vs MS-C) in sensorimotor and cognitive networks ( p range, ⩽0.001–0.01). Both HC groups showed decreased dFNC over time ( p range, ⩽0.001–0.01). Clinical improvements following interventions correlated with sensorimotor and cognitive dFNC changes, suggesting their possible role in motor recovery.